The BRICS Dilemma: A Polyheuristic Analysis of Indonesia's Free-Active Foreign Policy Shift - Dendy Raditya Atmosuwito; Yunus Ikhsan Bahari; Wibi - Lungidradityo (Global South Review, 2025)
This article examines the complex decision-making process behind Indonesia's pivotal shift to pursue full membership in the BRICS consortium. For decades, Indonesia, a prominent middle power, has navigated global politics through its "free and active" foreign policy, a doctrine rooted in the non-alignment principles of the 1955 Bandung Conference. This long-held stance created a significant dilemma when faced with an invitation to join BRICS, an alliance often perceived as a counterweight to Western-led global governance structures. This paper argues that Indonesia's ultimate decision to join under the Prabowo Subianto administration is not merely a product of rational economic and geopolitical calculations, but rather the result of a complex polyheuristic process. It posits that the primary shift occurred in the cognitive phase, where the leadership reconfigured the "free and "active" principle-previously a cognitive filter eliminating the membership option into a justification for proactive participation in a multipolar world. This reconceptualisation of the "critical dimension" allowed the membership option to pass into a second, more rational stage of analysis. Here, policymakers concluded that the long-term strategic benefits including economic diversification, access to alternative financing via the New Development Bank (NDB), and an enhanced role as a leader of the Global South outweighed the inherent risks of geopolitical friction and economic dependencies. This study utilises Polyheuristic Decision-Making Theory to deconstruct this shift, analysing how cognitive framing and rational calculus converged to produce a landmark foreign policy decision.